Evaluation of chemical methods for extracting available zinc in acid soils for coffee - Machado, Pedro Luiz Oliveira de Almeida; Pavan, Marcos Antonio (Pesquisa Agropecuaria Brasileira, 2014)
The response of coffee (Coffea arabica) seedlings to applied Zn on acid soils that had been limed to give a range of pH values was investigated in the greenhouse. Zinc sulfate was mixed with soils at the rate of 0, 5, 10 and 20 µg/g of Zn. The Zn content of the plants increased with Zn application and decreased with increasing pH. The solubility of Zn in the soils decreased markedly with increasing pH from four to seven. The order of extractability was 0.1N HCl > 0.05N HCl + 0.025N H2SO4 > NH4OAc 1N pH 4.8 > DTPA > EDTA > water soluble. The 0.1N HCl and double acid extractants gave higher correlation with Zn uptake under pH < 5.5. The efficiency of these acid extractants decreased with increasing pH. The DTPA and EDTA tended to be more indicative of Zn uptake by coffee plants under pH > 6.2 than acid solutions.